Mammographic Breast Density Profile of Jordanian Women With Normal and Breast Cancer Findings. (May 2020) - Al-Mousa, Dana S; Alakhras, Maram; Spuur, Kelly M; Alewaidat, Haytham; Rawashdeh, Mohammad; Abdelrahman, Mostafa; Brennan, Patrick C
Purpose: To document the mammographic breast density (MBD) distribution of Jordanian women and the relationship with MBD with age. Correlation between breast cancer diagnosis and density was also explored. Methods: A retrospective review of 660 screening mammograms from King Abdullah University Hospital was conducted. Mammograms were classified into 2 groups: normal (return to routine screening) and breast cancer and rated using the American College of Radiology (ACR) Breast Imaging-Reporting and Data System (BI-RADS) 5th edition for MBD. The association between MBD and age was assessed by descriptive analyses and Kruskal-Wallis test. To compare between normal and breast cancer groups, chi-square post hoc tests with Bonferroni adjustment was used. Results: Groups consisted of 73.9% (n = 488) normal group and 26.1% (n = 172) breast cancer group. A significant inverse relationship was demonstrated between age and MBD among the normal ( r = −.319, P < .01) and breast cancer group ( r = −.569, P < .01). In total, 69% (n = 336) of women in the normal group and 71% (n = 122) in the breast cancer group and 79.1% (n = 159) of the normal group and 100% (n = 48) of the breast cancer group aged 40 to 49 years reported high MBD (ACR BI-RADS c or d). Conclusions: Most of women in both the normal and breast cancer groups evidenced increased MBD. Increased MBD was inversely proportional to age. As MBD has a known link to increased breast cancer risk and the decreased sensitivity of mammography and it is vital that future screening guidelines for Jordanian women consider the unique breast density distribution of this population.